Bildwelten des Wissens : Kunsthistorisches Jahrbuch für Bildkritik. MUSEALE RESTE - Caviezel, Flavia; Christopher, Li; DeSilvey, Caitlin; Egger, Marie; Gineprini, Lorenzo; Gräfe, Sophia; Grünfeld, Martin; Hoffmann, Raphael; Kowal, Emma; Lowe, Adam; Macdonald, Sharon; Malanski, Andrea; et al. (Bildwelten des Wissens, 2022)
Remnants are a challenge for the museum as an institution. They are ambiguous figures, and their attributions open up and thus contribute to transcending the taxonomic, disciplinary, architectural, and institutional boundaries of museums. They can be found everywhere-in exhibition spaces as well as storage depots, and in laboratories just as in the administration. In each of these contexts, there are respectively different forms of professional self-conception, knowledge, and practical handling that determine the status of remnants. The volume contributes to specifying terms such as remnant, trash, traces, and boundaries more precisely within the context of the museum and to reassessing them for debates in conservation, curating, art history, and museum anthropology.